Ozonetherapy in Treatment of Oncological Patients (Ozone Therapy Global Journal, 2017)
The incidence of onco-gynecological diseases is one of the highest among female scourges involving different age groups. The primary importance at the early stages of treatment is conventionally given to surgical intervention followed by polychemio-therapy, hormonal and radial therapies. In these conditions the use of new methods that might correct the levels of antioxidant defense system and of lipid peroxidation as well as to modulate immunological response seems to be very promising. The aim of this study was to evaluate ozone effect on various homeostatic parameters in postoperative period. There have been examined 100 women with various onco-gynecological diseases (cervical carcinoma, ovarian carcinoma, endometrial carcinoma). All the patients were compatible according to the age and concomitant pathology and were operated for the pathology. Ozonetherapy course of 6 procedures, (ozone concentration of 400 µg/L in physiological saline) done intravenously every second day was administered to 60 women, starting on the second postoperative day. Patients of the control group (40 patients) were on conventional management without ozone administrationIn addition to clinical examination, all the patients were taken tests for intensity of serum lipid peroxidation according to the indices of chemilumenescence - primary (dien conjugates), secondary (trien conjugates) and final (Shiff bases) products and for general antioxidant activity. To evaluate the immune status the mononuclear cells of peripheral blood were immunophenotyped regarding the amount of CD 4, CD8, CD16, CD22, CD25, CD71, CD 38, CD95, HLA 1, HLA DR. The levels of soluble antigens: CD 50, CD95, CD38, CD54 as well as the antigens of the  histocompatible classes ( HLA -1  and HLA - 2) were also analyzed. Competitive solid-phase enzyme immunoassay was used to identify the levels of tumor necrosis factor (TNF) and of interleukin-2 (Il –2).Ozonetherapeutic procedures were not found to cause any complications. The clinical effect could be seen in improvement of appetite, better sleep, alleviation of nausea and weakness. All patients with elevated billirubin, fibrinogen and hepatic enzyme activity on having undergone the course of ozonetherapy were found to have these indices returning to baseline value. Initial laboratory results showed the increase in total antioxidant blood activity and the depression of lipid peroxidation processes. Taking into consideration ozone property at low concentration to improve the immunity and lipid peroxidation, ozone was used as a poliative remedy. Ozonetherapy proved to be very helpful in the management of chemiotherapy complications in patients with onco-gynecological pathology..